A prospective study of injury pattern and outcome of blunt trauma abdomen patients in a tertiary care hospital in eastern part of India - Pandey, Vinod Kumar; Shahi, Hanuman Prasad; Singh, Rahul; Pratap, Prakhar (International Surgery Journal, 2020)
Background: Abdominal trauma continues to account for a large number of trauma-related injuries and deaths. The evaluation and treatment of abdominal injuries are critical components in the management of severely injured trauma patients. The study was done to study pattern and outcome of BTA patients in a tertiary care hospital in eastern part of India as few studies exist in this part of the country. Methods: Prospective descriptive study conducted in in SRN Hospital, Prayagraj over a period of one year with all cases of blunt injury abdomen included with respect to inclusion criteria. Results: In our study mean age was 23.2±17.6 years. 92% were male and 8% were female RTA are responsible for most number of cases (78%). Conservative management done in 34 (68.0%) and Operative Intervention done in 16 (32.0%) cases. In our study, X-ray erect had 75% accuracy total subsets of 336 organ scans were performed on ultrasound specific injury was seen in total 50 cases and total 210 CT scans performed was able to pick up 59 injuries (p=0.0002). CECT forms the core investigation of choice in dealing with blunt injury abdomen cases. In our present study, paralytic ileus (prolonged) (31%) and pelvic intraabdominal abscess (31%) as postoperative complications. Conclusions: CECT abdomen is the investigation of the choice with RTA being the most common mode of BTA. So effort should be made to implement traffic rules. Hemodynamic instability with radiological findings useful in deciding operative versus conservative management of blunt trauma patients.